To play or not to play? The relationship between active video game play and electrophysiological indices of food‐related inhibitory control in adolescents. (19th December 2020) - Smith, Joshua L.; Carbine, Kaylie A.; Larson, Michael J.; Tucker, Larry A.; Christensen, William F.; LeCheminant, James D.; Bailey, Bruce W.
Abstract: Sedentary behaviors, such as computer use and sedentary video games, are barriers to physical activity, contribute to overweight and obesity among adolescents, and can adversely affect eating behaviors. Active video games may increase daily physical activity levels among adolescents and improve food‐related inhibitory control. We compared the effects of acute bouts of active and sedentary video gaming on event‐related potential (ERP) indices of food‐related inhibitory control, energy expenditure, and ad libitum eating. In a within‐subjects design, 59 adolescent participants (49% female, Mage  = 13.29 ± 1.15) completed two separate counterbalanced, 60‐min long video gaming sessions separated by seven days. Immediately after, participants completed two go/no‐go tasks with high‐ and low‐calorie images and N2 and P3 ERP amplitudes were measured. Participants also completed a Stroop task and were given high‐ and low‐calorie snacks to consume ad libitum. Results indicated that active relative to sedentary video games significantly increased energy expenditure on multiple measures (e.g., METs, heart rate, kcals burned) and participants consumed more calories after the active compared to the sedentary video game session. N2 amplitudes were larger when participants inhibited to high‐ compared to low‐calorie foods, suggesting that high‐calorie foods necessitate increased the recruitment of inhibitory control resources; however, there were non‐significant differences for the N2 or P3 amplitudes, accuracy or response times, and Stroop performance between active versus sedentary video game sessions. Overall, sixty minutes of active video gaming increased energy expenditure and food consumption but did not significantly alter neural or behavioral measures of inhibitory control to food stimuli. Abstract : Active versus sedentary video game play does not impact electrophysiological or behavioral indices of food‐related inhibitory control in adolescents. Active gaming increases energy expenditure and physical movement but does not change inhibitory control and may be associated with increased caloric intake.